Elaboração de glossários multimodais colaborativos das disciplinas de matemática e geografia do 8º ano do ensino fundamental - Santos, Luiz Fernando de Oliveira dos (2019)
Language, as a code, provides an interaction between individuals from one or more communities, establishing itself as the main support of culture and intergenerational transmission of knowledge. Teaching a language should consider the local social group’s customs, practices and experiences to build a strong relationship between language, society and culture. It is through the lexicon that the language users can express their ideologies, histories and expectations. When schools give formal education for their students, with focus on vocabulary development, it is common the contact with the dictionary, but, on the other hand, it is noticeable the difficulty in understanding local and specifics terms and their application in different situations. Considering this difficulties, the school plays a fundamental role of favoring, mobilizing and articulating the conditions for the socio-educational development, enabling students to deal efficiently with languages challenges. Being thus duly explained, this research claims to develop the expansion of vocabulary and understanding in the classroom, through the elaboration of a multimodal participative glossaries, one for each participant discipline, with terms and expressions pertaining to mathematical and geography texts of the 8th grade of the Fundamental Education of the Military College of Fortaleza, as a didactic support tool for the students. The main hypothesis of this research is that a multimodal glossary made by the 8th grade students will provide the expansion of the vocabulary framework of expressions in this kind of texts and would be an effective didactic support material. The theoretical study of this final paper is based on: knowledge of the lexicon science scope, Birdman (2001); Krieger (2006); Oliveira e Isquerdo (2001); Antunes (2012) e Aragão (2013); referring to the multimodalities and hypermodernities, considering Halliday´s (1985) contributions to this subject; Demo (2008); Dionisio (2011); Rosado & Bohadana (2007); Rojo (2015); concerning about theories of textual comprehension the study was based on the assumptions of Sim-Sim (2007) and, finally, about textual correction it is based on the studies of Cassany (1993); Serafini (1994) e Ruiz (1998). With regard to the collection and analysis procedure, this study is characterized as if an action research. As a form of pedagogical intervention, which seeks an effective didactic transposition to work in the classroom with systematically organized activities, a Teaching Sequence based on the principles and models framed by Schneuwly and Dolz (2004) will be proposed. The results obtained showed that: the vocabulary appropriation of the terms and expressions present in the classrooms of the subjects of Mathematics and Geography of the 8th year, by the students, was considered opportune; the written competence of the genre entry was evaluated very positively, in particular with the use of multimodal texts in a digital environment; and the glossary was confirmed as an important instrument of didactic support for students.